2016
DOI: 10.1080/13825585.2016.1226246
|View full text |Cite
|
Sign up to set email alerts
|

Perceived loneliness and general cognitive status in community-dwelling older adults: the moderating influence of depression

Abstract: The relationship between depression, loneliness, and cognitive functioning among the elderly is not well understood in the literature. In the present study, we tested the moderating influence of depressive symptoms on loneliness and cognitive functioning. We recruited 100 community-dwelling older adults in Hong Kong. Demographic information, perceived loneliness, depressed mood, and general cognitive status were assessed. Results indicated that married participants reported lower levels of perceived loneliness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Unlike our study one study also showed an association between loneliness and depressive symptomatology collected by the GDSVE-6 screening, which we also used in our study (59). Other recent research in depressed older adults showed loneliness as a risk factor, associated with both cognitive impairment and elevated mortality (67,68). Ausín et al,2017, identified several variables as predictive of loneliness in Spanish adults over sixty-five years of age, including functional deterioration and low satisfaction with QoL and social contacts, and the presence of mental disorders, especially anxiety (57).…”
Section: Discussionsupporting
confidence: 42%
“…Unlike our study one study also showed an association between loneliness and depressive symptomatology collected by the GDSVE-6 screening, which we also used in our study (59). Other recent research in depressed older adults showed loneliness as a risk factor, associated with both cognitive impairment and elevated mortality (67,68). Ausín et al,2017, identified several variables as predictive of loneliness in Spanish adults over sixty-five years of age, including functional deterioration and low satisfaction with QoL and social contacts, and the presence of mental disorders, especially anxiety (57).…”
Section: Discussionsupporting
confidence: 42%
“…Because loneliness and depression are strongly interrelated in older adults (Golden et al, 2009), depressed older adults might be particularly vulnerable for the poor health outcomes associated with loneliness. Supportive of this, loneliness in depressed older adults is associated with increased mortality rates (Stek et al, 2005;Holwerda et al, 2016), and in another study loneliness was associated with poor cognitive performance only in individuals with depressive symptoms (Lam, Yu, & Lee, 2017). Thus, in depressed older adults loneliness might be an important risk factor for cognitive decline.…”
Section: Loneliness and Cognitive Declinementioning
confidence: 83%
“…Donovan et al's (2017) study with 8,382 USA participants aged 65 or older concluded that, after 12 years, the effect of loneliness on cognitive function became marginally significant after controlling for depression, and that the latter is associated with a more rapid cognitive decline. Similarly, Lam et al (2017) revealed that, only among the individuals who reported higher levels of depressive symptoms, loneliness was associated with poorer cognitive function.…”
Section: Discussionmentioning
confidence: 94%